2002
DOI: 10.1086/338545
|View full text |Cite
|
Sign up to set email alerts
|

The Mauna Kea Observatories Near‐Infrared Filter Set. II. Specifications for a NewJHKLM′ Filter Set for Infrared Astronomy

Abstract: We present a description of a new 1-5 µm filter set similar to the long-used JHKLM filter set derived from that of Johnson. The new Mauna Kea Observatories Near-Infrared (MKO-NIR) filter set is designed to reduce background noise, improve photometric transformations from observatory to observatory, provide greater accuracy in extrapolating to zero air mass, and reduce the color dependence in the extinction coefficient in photometric reductions. We have also taken into account the requirements of adaptive optic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
351
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 435 publications
(355 citation statements)
references
References 15 publications
4
351
0
Order By: Relevance
“…NICS is equipped with a set of Mauna Kea Observatories near-infrared CH 4 s and CH 4 l filters as specified by Tokunaga et al (2002b) (as shown in Figure 1), and 1024x1024 Rockwell HAWAII-1 HgCdTe detectors.…”
Section: Observationsmentioning
confidence: 99%
“…NICS is equipped with a set of Mauna Kea Observatories near-infrared CH 4 s and CH 4 l filters as specified by Tokunaga et al (2002b) (as shown in Figure 1), and 1024x1024 Rockwell HAWAII-1 HgCdTe detectors.…”
Section: Observationsmentioning
confidence: 99%
“…In Table 1 we list the objects along with MKO magnitudes (Tokunaga et al 2002) and near-infrared (hereafter NIR) spectral types. The NIR spectral type classification follows the scheme described in Burgasser et al (2006a).…”
Section: Observations and Reduction Proceduresmentioning
confidence: 99%
“…Filters in the collimated beam are inclined by 5Њ to prevent "narcissus" ghost images from being refocused onto the detector. The other filter wheel in the converging beam is less susceptible to this type of ghost images and is therefore used for filters that were not designed for a 5Њ tilt, in particular for the "Mauna Kea standard" broadband filters (Tokunaga, Simons, & Vacca 2002).…”
Section: Camera Opticsmentioning
confidence: 99%